Analisis Tingkat Kepuasan Konsumen Terhadap Kualitas Produk Mi Nyemek Di Warkop Mitra 88 Menggunakan Metode Quality Function Deployment (QFD) - Erlangga, Muhammad Agung; Satriawan, I Ketut; Gunam, Ida Bagus Wayan (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Warkop Mitra 88 is a business in the food and beverage sector that began operations in 2024 and is required to maintain its position amidst competitors selling similar products, namely Mi Nyemek. The aim of this study is to identify the Mi Nyemek attributes considered important by consumers, analyze the importance and satisfaction levels of the Mi Nyemek product, and develop effective strategies to improve the quality of Mi Nyemek at Warkop Mitra 88. The research employs consumer satisfaction analysis using the Quality Function Deployment (QFD) method. The sample used in this study consists of 92 respondents. The findings reveal nine consumer importance attributes, with the highest importance value being the aroma attribute (4.03). Additionally, the attribute with the highest satisfaction level is price (4.35). The quality improvement strategy for Mi Nyemek prioritizes attributes with the highest improvement ratio values, namely maturity level, broth thickness, and aroma. Improvements are recommended in the technical parameters of product preparation, particularly in cooking Mi Nyemek, adding supplementary ingredients, and boiling noodles.